Non-covalent organocatalyzed enantioselective cyclization reactions of α,β-unsaturated imines - Torres-Oya, Sergio; Zurro, Mercedes (Beilstein Journal of Organic Chemistry, 2024)
Asymmetric cycloaddition is a straightforward strategy which enables the synthesis of structurally distinct cyclic derivatives which are difficult to access by other methodologies, using an efficient and atom-economical path from simple precursors. In recent years several asymmetric catalytic cyclization strategies have been accomplished for the construction of N-heterocycles using various catalytic systems such as chiral metal catalysts, chiral Lewis acids or chiral organocatalysts. This review presents an overview of the recent advances in enantioselective cyclization reactions of 1-azadienes catalyzed by non-covalent organocatalysts.
Keywords: α,β-unsaturated imines; asymmetric organocatalysis; cyclization; N-heterocycles; inverse electron demand aza-Diels–Alder reaction